2022
DOI: 10.3390/healthcare10122492
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effect of COVID-19 on Lung Imaging and Function, Cardiorespiratory Symptoms, Fatigue, Exercise Capacity, and Functional Capacity in Children and Adolescents: A Systematic Review and Meta-Analysis

Abstract: Background: The long-term sequela of COVID-19 on young people is still unknown. This systematic review explored the effect of COVID-19 on lung imaging and function, cardiorespiratory symptoms, fatigue, exercise capacity and functional capacity in children and adolescents ≥ 3 months after infection. Methods: A systemic search was completed in the electronic databases of PubMed, Web of Science and Ovid MEDLINE on 27 May 2022. Data on the proportion of participants who had long-term effects were collected, and on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Our data shows that one-third of LCC participants have not returned to their regular activities and 8% required help to complete their ADLs ≥3 months after infection. It has been observed that LCC affects patients’ physical function, ability to return to work, school or other regular activities, and impacts their health-related quality of life ( 8 , 38 ). However, to the best of our knowledge, this is the first study to identify that activity limitations were more likely to be reported by men and older participants.…”
Section: Discussionmentioning
confidence: 99%
“…Our data shows that one-third of LCC participants have not returned to their regular activities and 8% required help to complete their ADLs ≥3 months after infection. It has been observed that LCC affects patients’ physical function, ability to return to work, school or other regular activities, and impacts their health-related quality of life ( 8 , 38 ). However, to the best of our knowledge, this is the first study to identify that activity limitations were more likely to be reported by men and older participants.…”
Section: Discussionmentioning
confidence: 99%
“…Additional file 9 [ 40 , 69 , 75 , 97 , 108 , 109 , 117 , 122 , 123 , 132 , 137 ] summarizes single-arm evidence about COVID-19-associated MIS-C. Additional file 10 [ 62 , 156 , 157 ] summarizes single-arm evidence about newborns from COVID-19-diagnosed mothers. Additional file 11 [ 47 , 87 ] summarizes single-arm evidence about long-COVID. Additional file 12 [ 54 , 67 , 77 , 139 , 153 ] summarizes single-arm evidence about events caused by the COVID-19 vaccine.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, attributed to respiratory restriction and other reasons, exercise tolerance decreased by different proportions in different patient groups. Their quality of life and psychological assessment results also demonstrated they were influenced at different degrees ( 35 , 39 ). In a number of case reports about pulmonary function, the assessment of children cases after recovering from COVID-19 did not show a significant impact, different from the generally impaired pulmonary function of adults.…”
Section: Clinical Manifestation Of Long Covid In Different Systemmentioning
confidence: 98%